Workers' organizations and the fetishism of the trade union form: toward new pathways for research on the labour movement?. Issue 8 (17th November 2021) - Atzeni, Maurizio
ABSTRACT: In the field of labour studies and industrial relations, there's a long-standing tradition, common to both the reformist and Marxist left, of focusing the analysis on the trade unions, the par excellence form of workers' organization. Changes in the global political economy in the past decades have completely altered the productive and social landscape in which trade unions have historically been inserted questioning the extent to which existing trade unions are still representative of broader working-class interests. I argue that despite this adverse context, labour relations research on collective organization and conflict has remained trapped into a logic which I call, paraphrasing Marx, of trade union fetishism. My critique is a methodological call to abandon the comfort zone of the capital labour relation and of its 'symbiotic relationship' with trade unions to advance the field of study toward a truly working-class analysis, based on actually existing social processes of struggle.